2006
DOI: 10.1093/eurheartj/ehl177
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gln222Arg polymorphism in the deoxyribonuclease I (DNase I) gene with myocardial infarction in Japanese patients

Abstract: Our data demonstrate that Gln222Arg polymorphism in the DNase I gene is associated with MI in the Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…40 A single-nucleotide polymorphism in the DNase-1 gene, which leads to impaired DNase activity, was independently associated with a higher incidence of myocardial infarction. 41 In animal models, medicinal DNase was successfully used to prevent venous thrombogenesis. 10 Inhibiting peptidylarginine deiminase 4, a key factor in NETosis, prolonged time to carotid artery thrombosis in a photochemical injury model.…”
Section: Discussionmentioning
confidence: 99%
“…40 A single-nucleotide polymorphism in the DNase-1 gene, which leads to impaired DNase activity, was independently associated with a higher incidence of myocardial infarction. 41 In animal models, medicinal DNase was successfully used to prevent venous thrombogenesis. 10 Inhibiting peptidylarginine deiminase 4, a key factor in NETosis, prolonged time to carotid artery thrombosis in a photochemical injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Less functional polymorphisms of DNase I exist in the human population 33, 34 . These polymorphisms or the presence of inhibitors impairing DNase 1 function 35 predisposes individuals to cardiovascular and autoimmune disease, likely because DNA (NETs) are not dismantled and removed in a timely manner 33–35 .…”
mentioning
confidence: 99%
“…Previously, we clarified the allele distribution of four (three in DNase 1L1 and one in DNase 1L2) non-synonymous SNPs and demonstrated that the non-synonymous ones identified in the DNase 1L1 and 1L2 genes may exert no influence on the activity levels of DNases 1L1 and 1L2 in human [14]. Human DNases have been investigated for their involvement in the pathophysiology of various diseases as genetic factors [13,[15][16][17]. In this context, the clarification of genetic aspects of all SNPs, including synonymous ones in the DNase 1L1 and 1L2 genes, would allow us to gain a comprehensive understanding of the association of DNase 1L1 and/or 1L2 with the risk of various diseases as the genetic background of disease susceptibility.…”
mentioning
confidence: 99%